ANALYSIS OF THE EFFECT OF PERSON ORGANIZATION FIT AND PERSON JOB FIT IN IMPROVING JOB SATISFACTION PERFORMANCE OF HEALTH SERVICE EMPLOYEES IN NGASEM COMMUNITY HEALTH CENTER, KEDIRI REGENCY IN 2024 - Aris Dwi C.; Luluk S.; Fannidya H.Z.; Suryono (Suluh Adiluhung Publisher (SAPub), 2025)
The complex role and function of the Community Health Center requires the availability of competent human resources at the Community Health Center. Therefore, Person job fit needs to be applied to adapt to employees' abilities in motivating their performance to achieve organizational goals. The aim of this research is to determine the influence of person organization fit and person job fit in increasing job satisfaction on the performance of health service employees at the Ngasem Community Health Center, Kediri Regency. Data analysis in this research used the Partial Least Square (PLS) method. PLS can be used on all types of data scales (nominal, ordinal, interval, ratio) as well as more flexible assumption requirements. PLS is a structural equation model (SEM) that is component or variant based. that person-organization fit has an insignificant effect on job satisfaction. Person-organization fit has no effect on job satisfaction in this research sample, so H1 which states that person-organization fit has a significant positive effect on job satisfaction is not supported. Person-job fit has an effect on job satisfaction in this research sample, so that H2 which states that person-job fit has a significant positive effect on job satisfaction is supported. The suggestion in this research is to re-evaluate the introduction of organizational values ​​so that they can be understood well by employees. Provide training related to emotional labor management to employees.